Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Certainly! Let's address both parts of the question using the given set of potential values for [tex]\( a \)[/tex]: [tex]\( \{1, -1, 2, -2, 3, -3\} \)[/tex].
### Part (i) [tex]\( \frac{1}{a} = 1 \)[/tex]?
First, let’s verify the expression [tex]\( \frac{1}{a} = 1 \)[/tex] for each value of [tex]\( a \)[/tex]:
1. For [tex]\( a = 1 \)[/tex]:
[tex]\[ \frac{1}{1} = 1 \][/tex]
This is true.
2. For [tex]\( a = -1 \)[/tex]:
[tex]\[ \frac{1}{-1} = -1 \][/tex]
This is not true.
3. For [tex]\( a = 2 \)[/tex]:
[tex]\[ \frac{1}{2} = 0.5 \][/tex]
This is not true.
4. For [tex]\( a = -2 \)[/tex]:
[tex]\[ \frac{1}{-2} = -0.5 \][/tex]
This is not true.
5. For [tex]\( a = 3 \)[/tex]:
[tex]\[ \frac{1}{3} = 0.3333\ldots \][/tex]
This is not true.
6. For [tex]\( a = -3 \)[/tex]:
[tex]\[ \frac{1}{-3} = -0.3333\ldots \][/tex]
This is not true.
From these computations, we conclude that [tex]\( \frac{1}{a} = 1 \)[/tex] only holds for [tex]\( a = 1 \)[/tex] and does not hold for other given values of [tex]\( a \)[/tex].
### Part (ii) [tex]\( \frac{a}{-1} = -a \)[/tex]?
Now, let’s check the expression [tex]\( \frac{a}{-1} = -a \)[/tex] for each value of [tex]\( a \)[/tex]:
1. For [tex]\( a = 1 \)[/tex]:
[tex]\[ \frac{1}{-1} = -1 \][/tex]
This is true.
2. For [tex]\( a = -1 \)[/tex]:
[tex]\[ \frac{-1}{-1} = 1 \][/tex]
This is true.
3. For [tex]\( a = 2 \)[/tex]:
[tex]\[ \frac{2}{-1} = -2 \][/tex]
This is true.
4. For [tex]\( a = -2 \)[/tex]:
[tex]\[ \frac{-2}{-1} = 2 \][/tex]
This is true.
5. For [tex]\( a = 3 \)[/tex]:
[tex]\[ \frac{3}{-1} = -3 \][/tex]
This is true.
6. For [tex]\( a = -3 \)[/tex]:
[tex]\[ \frac{-3}{-1} = 3 \][/tex]
This is true.
From these computations, we confirm that [tex]\( \frac{a}{-1} = -a \)[/tex] holds true for all the given values of [tex]\( a \)[/tex].
### Conclusion
- For part (i) [tex]\( \frac{1}{a} = 1 \)[/tex]: This holds true only when [tex]\( a = 1 \)[/tex].
- For part (ii) [tex]\( \frac{a}{-1} = -a \)[/tex]: This holds true for all the given values of [tex]\( a \)[/tex].
### Part (i) [tex]\( \frac{1}{a} = 1 \)[/tex]?
First, let’s verify the expression [tex]\( \frac{1}{a} = 1 \)[/tex] for each value of [tex]\( a \)[/tex]:
1. For [tex]\( a = 1 \)[/tex]:
[tex]\[ \frac{1}{1} = 1 \][/tex]
This is true.
2. For [tex]\( a = -1 \)[/tex]:
[tex]\[ \frac{1}{-1} = -1 \][/tex]
This is not true.
3. For [tex]\( a = 2 \)[/tex]:
[tex]\[ \frac{1}{2} = 0.5 \][/tex]
This is not true.
4. For [tex]\( a = -2 \)[/tex]:
[tex]\[ \frac{1}{-2} = -0.5 \][/tex]
This is not true.
5. For [tex]\( a = 3 \)[/tex]:
[tex]\[ \frac{1}{3} = 0.3333\ldots \][/tex]
This is not true.
6. For [tex]\( a = -3 \)[/tex]:
[tex]\[ \frac{1}{-3} = -0.3333\ldots \][/tex]
This is not true.
From these computations, we conclude that [tex]\( \frac{1}{a} = 1 \)[/tex] only holds for [tex]\( a = 1 \)[/tex] and does not hold for other given values of [tex]\( a \)[/tex].
### Part (ii) [tex]\( \frac{a}{-1} = -a \)[/tex]?
Now, let’s check the expression [tex]\( \frac{a}{-1} = -a \)[/tex] for each value of [tex]\( a \)[/tex]:
1. For [tex]\( a = 1 \)[/tex]:
[tex]\[ \frac{1}{-1} = -1 \][/tex]
This is true.
2. For [tex]\( a = -1 \)[/tex]:
[tex]\[ \frac{-1}{-1} = 1 \][/tex]
This is true.
3. For [tex]\( a = 2 \)[/tex]:
[tex]\[ \frac{2}{-1} = -2 \][/tex]
This is true.
4. For [tex]\( a = -2 \)[/tex]:
[tex]\[ \frac{-2}{-1} = 2 \][/tex]
This is true.
5. For [tex]\( a = 3 \)[/tex]:
[tex]\[ \frac{3}{-1} = -3 \][/tex]
This is true.
6. For [tex]\( a = -3 \)[/tex]:
[tex]\[ \frac{-3}{-1} = 3 \][/tex]
This is true.
From these computations, we confirm that [tex]\( \frac{a}{-1} = -a \)[/tex] holds true for all the given values of [tex]\( a \)[/tex].
### Conclusion
- For part (i) [tex]\( \frac{1}{a} = 1 \)[/tex]: This holds true only when [tex]\( a = 1 \)[/tex].
- For part (ii) [tex]\( \frac{a}{-1} = -a \)[/tex]: This holds true for all the given values of [tex]\( a \)[/tex].
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.